Rapid and Systematic Access to Quasi-Diblock Copolymer Libraries Covering a Comprehensive Composition Range by Sequential RAFT Polymerization in an Automated Synthesizer - Haven, Joris J.; Guerrero-Sanchez, Carlos; Keddie, Daniel J.; Moad, Graeme (Macromolecular rapid communications., 2014)
A versatile, cost‐effective approach to the rapid, fully unattended preparation of systematic quasi‐diblock copolymer libraries via sequential RAFT polymerization in an automated synthesizer is reported. The procedure is demonstrated with the synthesis of a 23 member library of low dispersity poly(butyl methacrylate)‐quasiblock‐poly(methyl methacrylate) covering a wide (fivefold) range of molar mass for the second block in a one‐pot, sequential, RAFT polymerization. A versatile, cost‐effective approach to the rapid, fully unattended preparation of systematic quasi‐diblock copolymer libraries by sequential RAFT polymerization in an automated synthesizer is reported.